PENGARUH KEPEDULIAN ORANG TUA TERHADAP MINAT BERIBADAH ANAK KELAS EMPAT SAMPAI ENAM SEKOLAH DASAR DI SEKOLAH MINGGU GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - Gomgom Purba; Carolina Carolina (JURNAL IMPARTA, 2023)
Sunday school is one of the teaching and guiding methods for children to learn about Christ through various creative activities that can enhance their interest in attending worship every Sunday. Parents play a significant role in nurturing their children's spiritual growth. The research conducted using quantitative methods shows that the level of Parental Concern falls within the low to moderate category, with a significance level of α 0.05. Specifically, it falls within the range of 57.17 – 60.89, indicating a low to moderate level. Therefore, the level of parental concern for Sunday school children at the Bethel Indonesia Tabgha Batam Center is still relatively low and needs improvement. The percentage of the influence of parental concern (X) on children's interest in attending Sunday school (Y) is 63.5%. The remaining 36.5% is influenced by other variables not included in this research model. The constant is 22.673, meaning that if parental concern (X) is 0, the interest of children in attending Sunday school at the Bethel Indonesia Tabgha Batam Center is 22.673 units. The regression coefficient for parental concern (X) is 0.709, indicating that increasing parental concern by one unit will lead to a 0.709-unit increase in children's interest in attending Sunday school (Y). Based on the research findings, the researcher suggests several programs to improve parental concern towards children's interest in attending Sunday school at the Bethel Indonesia Tabgha Batam Center, hoping that these proposed programs will serve as solutions for enhancing parental concern.